On the Methodology of Modern Russian Law - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2023)
An analysis of modern Russian literature made it possible to identify two equally negative tendencies in the methodology of jurisprudence. The first is that legal scholars pay little attention to methodology; the second is in attempts to introduce new methods into the methodology that are not used in practice.